Performance of Ground Anchored Walls Subjected to Dynamic and Pseudo-Static Loading - Saeidi Rashk Olia, Arash; Oliaei, Mohammad; Heidarzadeh, Heisam (Salehan Institute of Higher Education, 2021)
This study investigates the response of pre-stressed anchored excavation walls under dynamic and pseudo-static loadings. A finite difference numerical model was developed using FLAC2D, and the results were successfully validated against full-scale experimental data. Analyses were performed on 10, and 20-m-height stabilized excavated slopes with 60Â° to 90Â° of inclination angle with the horizon to represent an applicable variety of wall geometries. In dynamic analysis, the statically stabilized models were subjected to 0.2 to 0.6g of the dynamic peak acceleration to evaluate the effect of ground acceleration on their performance. Furthermore, pseudo-static analyses were performed on the statically stabilized models with pseudo-static coefficients ranging from 0.06 to 0.22. The results revealed that ground anchored slopes generally showed acceptable performances under dynamic loading, while higher axial forces were induced to ground anchors in higher and steeper models. Furthermore, comparing the results of dynamic and pseudo-static analyses showed a good agreement between the two methods' predictions in the mobilized axial force along the ground anchors. Pseudo-static coefficients were then proposed to replicate dynamic results, considering the slope geometry and dynamic load peak acceleration. The results revealed that higher and steeper stabilized slopes required higher values of pseudo-static coefficients to match the dynamic predictions successfully. The results indicate that pseudo-static coefficient tend to increase with the increase in dynamic load peak acceleration in any given model.Â Doi: 10.28991/cej-2021-03091703 Full Text: PDF